Cauda Equina Syndrome secondary to sacral chordoma: a case report - Abu Hasan, Muhammad Abdus-Syakur; Hassan, Muhammad Afiq (Malaysian Journal of Emergency Medicine, 2025)
Introduction: Cauda equina syndrome (CES) is a rare yet urgent neurosurgical condition characterized by the compression of cauda equina nerve roots, leading to potentially irreversible neurological deficits if untreated. While lumbar disc herniation is the most common cause, rare entities like sacral chordoma can also result in CES. Sacral chordomas are malignant tumors originating from notochord remnants, often presenting with vague symptoms that delay diagnosis. This case report highlights an atypical presentation of CES secondary to sacral chordoma, emphasizing the importance of early recognition, imaging, and surgical intervention.